Response of clove (Syzygium aromaticum (L.) Merr. & Perry) seedlings and black pepper (Piper nigrum L.) cuttings to propagating media under nursery conditionsl - KANDIANNAN, C K THANKAMANI, K SIVARAMAN, K (Journal of Spices and Aromatic Crops, 1996)
Various propagating media were evaluated for enhancing growth of clove (Syzygium aromaticum L.) seedlings in the nursery and the best was soil and vermicompost mixed in 1 : 1 proportion. The transplanting time of clove seedlings could also be shortened to 1 year by adopting this media in the nursery. Vermicompost was also evaluated as a propagating media for black pepper (Piper nigrum L.) in comparison with potting mixture comprising of soil, sand and farmyard manure. Black pepper "uttings raised in vermicompost were significantly taller and had more number of leaves than in potting mixture.